The species of Trite Simon, 1885 (Araneae: Salticidae) from New Caledonia - Patoleta, Barbara M. (Zootaxa, 2014)
The male holotype of Trite lineata Simon, 1885 is redescribed and the palp is illustrated for the first time. The female is formally described. Three new species are diagnosed, described and illustrated: Trite caledoniensis sp. nov., T. guilberti sp. nov. and T. simoni sp. nov. Remarks on distribution and relationships of the genus are given.